1985
DOI: 10.1021/jo00221a043
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom cyclopentene annulation. Synthesis of guaiane ring system

Abstract: The investigation of Verbesina sphaerocephala afforded an amorphane 7-lactol; the structure was established by interpretation of spectral data and X-ray diffraction analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Ozonolysis of these dienes followed by reductive workup then yielded a mixture of the dicarbonyl products and their methanol acetals [2]. Treatment of each mixture with 3% aqueous perchloric acid in tetrahydrofuran (1:1 v/v) [10] gave the required nitro dicarbonyl substrates. The results of our reductive cyclization studies are shown in Scheme 2 [11].…”
Section: Resultsmentioning
confidence: 99%
“…Ozonolysis of these dienes followed by reductive workup then yielded a mixture of the dicarbonyl products and their methanol acetals [2]. Treatment of each mixture with 3% aqueous perchloric acid in tetrahydrofuran (1:1 v/v) [10] gave the required nitro dicarbonyl substrates. The results of our reductive cyclization studies are shown in Scheme 2 [11].…”
Section: Resultsmentioning
confidence: 99%
“…Prior to reductive cyclization, this mixture was treated with 3% perchloric acid:tetrahydrofuran (1:1) at 0°for 1 hour and at room temperature for 12 hours, then extracted (two times) with dichloromethane [12]. The organic layer was washed with sodium bicarbonate and sodium chloride, dried (magnesium sulfate), and concentrated under vacuum to give 970 mg (5.71 mmole, 96%) of 4c as a light yellow oil; ir: 2830, 2722, 1721 cm -1 ; 1 H nmr: δ 9.76 (t, 1H, J = 1.4), 2.47 (m, 2H), 2.38 (t, 2H, J = 7.4), 1.90 (quintet, 2H, J = 7.1), 1.65 (m, 1H), 1.57 (quintet, 2H, J = 7.4), 1.28 (m, 5H), 0.89 (t, 3H, J = 7.1); 13 C nmr: δ 210.…”
Section: Jan-feb 2003 117mentioning
confidence: 99%
“…Since trace amounts of acid produced in the ozonolyses led to the formation of cyclic peroxides from the alkyl 3-butenyl ketones [11], reactions of 1a-i were performed in the presence of catalytic sodium bicarbonate [9a] and the crude ozonolysates were used directly in the hydrogenation. The ozonolyses of 3a-i, 5a-c and 7a-b to prepare 5-oxoaldehydes were less susceptible to cyclization and were carried out using our previously described procedure [7,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vacuum filtration and concentration under reduced pressure gave the dimethyl acetal 3 containing 5-10% of aldehyde 4. This mixture was dissolved in 25 mL of tetrahydrofuran, cooled to 0˚, and 25 mL of 3% aqueous perchloric acid was added dropwise with stirring [10]. The solution was stirred at 0f or 1 hour and at room temperature for 4 hours, then extracted with dichloromethane (three times).…”
Section: Introductionmentioning
confidence: 99%